2023
DOI: 10.1371/journal.pone.0279819
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the risk factors associated with implementing projects of health information technology by fuzzy combined ANP-DEMATEL

Abstract: Background Application of a Clinical Information System (CIS) like Electronic Patient Record (EPR), PACS system and CPOE has turned into one of the most important criteria of priorities of health care systems. The aims of the clinical information system include improving the physicians’ efficiency level, integrating the caring process, and expanding the fuzzy quality of the services offered to patients. Achievement of these benefits in reality is not an easy task, and there are lots of plans in this field whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the existing conditions, applying DEMATL and ANP revealed that the most influential factors on patients' operating suite LOS in order of significance are the main surgical procedure, surgical set preparation, patient pre-op waiting time, anesthesia, and patient preparation, respectively. In the other studies, Göncü and Çetin [ 30] developed a model by using the DEMATEL and ANP to select supplier in the health care, and Sharifian et al, [31] employed ANP-DEMTEL combined approach to evaluate the risks of implementing the projects of clinical information technology in hospitals. As seen in Table 5, the identification of factors using the AAA method has resulted in significantly better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing conditions, applying DEMATL and ANP revealed that the most influential factors on patients' operating suite LOS in order of significance are the main surgical procedure, surgical set preparation, patient pre-op waiting time, anesthesia, and patient preparation, respectively. In the other studies, Göncü and Çetin [ 30] developed a model by using the DEMATEL and ANP to select supplier in the health care, and Sharifian et al, [31] employed ANP-DEMTEL combined approach to evaluate the risks of implementing the projects of clinical information technology in hospitals. As seen in Table 5, the identification of factors using the AAA method has resulted in significantly better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Sharifian et al, [31] conducted an applied study that evaluates the risk factors related to the implementation of clinical information technology projects in the hospital. Fuzzy logic was used in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…F-DEMATEL provides insights into how factors earmarked for decision making can be prioritized as with other multi-criteria decision methods. This study used the F-DEMATEL method because it can illustrate the causal relationships among the factors while overcoming ambiguity, subjectivity, and uncertainty, which are typical in many decision settings [ 68 ]. Whereas other variations of DEMATEL, such as Grey DEMATEL, could also be utilized, these approaches primarily focus on solving problems in systems with inadequate information or imprecise data [ 69 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study assessed relationships among unclear criteria involving linguistic variables and qualitative data. Coupled with the need to minimize the subjectivity of experts in the rating process [ 19 , 68 ], the researchers applied the F-DEMATEL method in this study. The results provide insights into which factors ought to be prioritized if altruistic messages are to be anchored by their recipients.…”
Section: Methodsmentioning
confidence: 99%
“…It is especially useful in analyzing the causeand-effect relationships between factors of the system and also to find the critical factors of a system [10]. DEMATEL has received a great deal of attention, and it is a widely used method in various fields, such as engineering [11,12], management sciences [13,14], medicine [15], COVID-19 [16][17][18], energy [19,20], urbanization [21,22], ecology [23,24], and others. It is also one of suitable methods to deal with the degree of importance of evaluation factors and to determine the cause-effect relationships between factors [25].…”
Section: Introductionmentioning
confidence: 99%